A Causal and Correlation Analysis between China Energy Futures and China Energy-Related Companies Stock Market. (30th June 2021) - Liu, Yufang; Zhang, Chi; Zhang, Wang
Abstract : Taking the opportunity of China's launch of Shanghai crude oil futures (INE), this study empirically examined the information transmission in this immature financial market, investigating this issue from a new perspective. To identify the impact of INE on the related stock market, we collected high-frequency trading data of oil futures and 22 stocks owned by listed companies in the upstream and downstream of China's oil-related industry chains, constructed a causal chain through Directed Acyclic Graph, and used MFDCCA-MODWT to perform multifractal analysis on the chain. Research shows that INE does have a causal relationship with the stock market of the related industry chain, and there is a multifractal correlation between its transaction time series. Subsequently, the source of fractal correlation was analysed with shuffled and surrogated sequences. We conclude that long memory plays a leading role and is the main reason for multifractal features.